"Being and Becoming" a Researcher: Building a Reflective Environment to Create a Transformative Learning Experience for Undergraduate Students. (October 2016) - Nye, Adele; Clark, Jennifer
This article discusses the processes and outcomes of inviting a group of undergraduate students to inhabit and then reflect upon peripheral learning spaces in university through a "publishing with students" exercise during an Undergraduate Research Summer School. The students engaged in conversation, discussion, reflection, and writing related to their experiences of realizing that they could become researchers. The emergent collegial dialogues crossed and intertwined traditional pathways and signposts for usual academic progression, reaffirming the value of creating alternative and irregular opportunities where transformative learning can occur.